Pengaruh Ukuran Perusahaan, Ukuran Kap, Komite Audit, Resiko Perusahaan, Dan Profitabilitas Terhadap Audit Fee Pada Perusahaan Jasa Sektor Property, Real Estate, And Building Construction Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Dedy Putra Naibaho; Melisa Melisa; Lavinia Fransiska; Annisa Nauli Sinaga (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to find out the influence of company size, accounting firm size, audit committee, company risk, and profitability on audit fee in the property, real estate, and building construction service companies that listed on Indonesian Stock Exchange (IDX). There are 24 companies as sample with total of 72 data. Variables of company size, accounting firm size, audit committee, company risk, and profitability tested by using multiple linier regression, classic assumption test, and hypothesis testing. According to simultaneous test company size, accounting firm size, audit committee, company risk, and profitability have significant effect towards audit fee. Coefficient of determination test shown 0,592 can be interpreted that influence of company size, accounting firm size, audit committee, company risk, and profitability towards audit fee is 59,2%. The another 40,8% were influenced of other variables that were not mentioned. Keywords : Company Size, Accounting Firm Size, Audit Committee, Company Risk, Profitability, Audit Fee